Oxymatrine ameliorates experimental autoimmune encephalomyelitis by rebalancing the homeostasis of gut microbiota and reducing blood-brain barrier disruption - Zhang, Ming-Liang; Li, Wei-Xia; Wang, Xiao-Yan; Wu, Ya-Li; Chen, Xiao-Fei; Zhang, Hui; Yang, Liu-Qing; Wu, Cheng-Zhao; Zhang, Shu-Qi; Chen, Yu-Long; Feng, Ke-Ran; Wang, Bin; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Increasing evidence suggests that gut dysbiosis can directly or indirectly affect the immune system through the brain-gut axis and play a role in the occurrence and development of Multiple sclerosis (MS). Oxymatrine (OMAT) has been shown to ameliorate the symptoms of MS in the classical experimental autoimmune encephalomyelitis (EAE) model of MS but whether its therapeutic role is through the correction of gut dysbiosis, is unclear. In this investigation, we evaluated the effects of OMAT on intestinal flora and short chain fatty acids in EAE model mice, and further tested the functions of blood-brain barrier and intestinal epithelial barrier. The results revealed the alpha and beta diversity in the faeces of EAE mice were significantly different from that of the control group but recovered substantially after OMAT treatment. Besides, the OMAT treatment significantly affected the gut functional profiling and the abundance of genes associated with energy metabolism, amino acid metabolism, immune system, infectious diseases, and the nervous system. OMAT also decreased the levels of isobutyric acid and isovaleric acid in EAE mice, which are significantly related to the abundance of certain gut microbes and were consistent with the reduced expression of TNF-α, IL-6, and IL-1β. Furthermore, OMAT treatment significantly increased the expression of ZO-1 and occludin in the brains and colons of EAE mice and decreased blood-brain barrier permeability. OMAT may alleviate the clinical and pathological symptoms of MS by correcting dysbiosis, restoring gut ecological and functional microenvironment, and inhibiting immune cell-mediated inflammation to remodel the brain-gut axis.